Materalistic Thoughts Among People (Global Journal of Management and Business Research, 2012)
The focus of this research study is to see the level of materialistic thoughts among the people. Now people value to extrinsic things rather than intrinsic. Enjoyment, physical pleasure, material possessions and comfort are now becoming necessities of life. This study was conducted in January-June 2010. To analyze the materialistic thoughts among people five variables money, poverty, personal happiness, advertisement and culture were used as measurement tools to find materialistic thoughts among housewives, students, businessmen and salary person. Questionnaire was developed which includes demographic portion which was with some open and some close ended questions. Questions related to variables were all close ended. Stratified random sampling technique was used. Sample size was of 200. In results, there was no association between money, advertisement, poverty, culture, personal happiness with Study group. The materialistic thought is increasing among people due to two factors money and advertisement. Under recommendation it#x2019;s said that all that glitters is not gold so we should not give importance to luxurious things.
Keywords: Materialism; Materialistic Person; Money; Advertisement; Poverty; Culture; and Personal Happiness